2023
DOI: 10.12968/jowc.2023.32.5.318
|View full text |Cite
|
Sign up to set email alerts
|

The role of probiotics as wound healers: an overall view

Abstract: A wound is an injury to the skin or damage to the body tissue. The healing process differs between various kinds of wounds. Treatment of hard-to-heal (chronic) wounds becomes challenging for healthcare practitioners, especially if patients have underlying health complications such as diabetes. Infection of wounds is another factor that interferes with the healing process and extends its duration. Active research is being conducted into the development of advanced wound dressing technologies. These wound dressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…In this stage, lasting several weeks after injury, the granulating tissue matures and becomes a scar of high tensile strength, in parallel exerting higher resistance and flexibility. Matrix metalloproteases break down collagen III and replace it with collagen I, the primary collagen subtype in scar tissue, which further re-organizes into parallel fibrils, forming a low cellularity scar [58,62,64,66]. Since our data on probiotics is mainly based on cell cultures and excisional wound models in experimental animals, there is no published information on the long-term effects of probiotics in the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…In this stage, lasting several weeks after injury, the granulating tissue matures and becomes a scar of high tensile strength, in parallel exerting higher resistance and flexibility. Matrix metalloproteases break down collagen III and replace it with collagen I, the primary collagen subtype in scar tissue, which further re-organizes into parallel fibrils, forming a low cellularity scar [58,62,64,66]. Since our data on probiotics is mainly based on cell cultures and excisional wound models in experimental animals, there is no published information on the long-term effects of probiotics in the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120]. Both the above [115][116][117][118][119][120] may not have a direct, suppressive effect on the pain originating from abdominal wall trauma, or from the distension of the gut wall, but there are many studies documenting the specific cytokine and other molecular changes which point in that direction.…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 98%
“…According to the current definition, "probiotics are live microorganisms that, when administered in adequate amounts, confer a health effect on the host" [114]. Today, many in vitro and in vivo studies have shown that probiotics exert potential suppressive effects on various infectious and inflammatory conditions, thus significantly shortening the inflammatory phase of the wound healing process [115][116][117]. At the same time, there are quite a lot of clinical studies referring to the reduction in postoperative bloating and the shortening of the time duration up to the first flatus, all indirectly indicating the shortening of the postoperative paralytic ileus [118][119][120].…”
Section: Probiotics In Postoperative Pain Managementmentioning
confidence: 99%
“…The development of wound dressing technology has yielded promising findings due to its capacity to provide barriers and to promote healing through immune modulation and tissue regeneration of several (non-)infected wounds [ 75 ].…”
Section: Wound Dressings With Probiotics and Prebioticsmentioning
confidence: 99%